Débit énergétique et implications des filières anaérobie lactique et aérobie lors d`un slalom géant chez l`enfant skieur compétiteur - Grenier, J.G.; Hintzy, F.; Antichan, F.; Coulmy, N. (Science & Sports, 2013)
Purpose: To quantify the net energy expenditure and the respective implications of the aerobic and lactic energy sources over a giant slalom (GS) performed in the field in young ski racers. Methods: Seven young alpine skiing competitors (14.0 ± 0.5 years) volunteered to participate in the study. An inclusion session consisted of an evaluation of their peak oxygen consumption using a standardized incremental maximal aerobic test. Then, oxygen consumption was measured during an in situ GS. In addition, blood lactate concentrations were measured before and 2 minutes after the GS to determine the respective implications of the aerobic and lactic energy sources. Results: At the end of the SG, lasting 76.4 ± 10.9 seconds, oxygen consumption was 64.0 ± 7.8% of the peak oxygen consumption and blood lactate concentration was 5.7 ± 2.2 mmol/L. The total net energetic expenditure was 31.7 ± 6.7 kJ/min. Aerobic and lactic energy sources implications were 69.7 ± 16.7% and 30.3 ± 16.7%, respectively. Conclusion: In comparison with previous values reported in adults, young ski racers show low levels of total energy expenditure while performing a GS. The ability to increase the total energy expenditure seems to be influenced by the lactic energy source involvement.